(NvIWI I POMNI(B:s (NpOWESTI(B. (NrASSKAZYs - (NrASPUTIN w(B.s ((NwALENTIN gRIGORXEWI^(B)s ((NmOSKWA(B:s (Nast(B,s, 2004)
(Nw KNIGU WO[LI POWESTI w(B. (Ng(B. (NrASPUTINA (B"(NdENXGI DLQ mARII(B", "(NvIWI I POMNI(B", (NA TAKVE RASSKAZY (B"(NuROKI FRANCUZSKOGO(B", "(NwEK VIWI (B- (NWEK L@BI(B" (NI DR(B.s
(NiNW(B.: 41685s
(NtIRAV(B: 4000 (N\KZ(B.s
Keywords: (NDENXGI DLQ mARIIs -- (NUROKI FRANCUZSKOGOs -- (NNEVDANNO(B-(NNEGADANNOs